Implications of Integrating Nutrigenomic Aspects on Training Ability and Recovery in Athletes: A Literature Review - I Putu Gede Windhu Saputra (PT BMW Journal Sejahtera, 2024)
Introduction: Nutrition impacts sports performance significantly, influencing each athlete differently. Factors such as age, ethnicity, and genetics affect how athletes respond to nutrition. This review investigates how incorporating nutrigenomics enhances training and recovery in athletes. Methods: A systematic search following PRISMA 2020 guidelines was conducted to find relevant studies that examine the impact of genetic variations on nutritional effects related to athletic performance and recovery. The included articles are non-observational studies selected based on specific inclusion and exclusion criteria and were qualitatively analyzed. Results: The review included nine studies, primarily clinical and randomized controlled trials, conducted in Iran, Brazil, and Canada. Most studies focused on male athletes aged 15 to 40 years. The studies suggest that caffeine and vitamin D effects on performance may vary based on individual genotypes, but specific genes do not consistently influence these effects. Conclusion: Adopting genetic-based nutrition and supplementation approaches holds promising potential for optimizing athletic performance by tailoring nutrient intake to individual genetic profiles.